Upregulated long noncoding RNA Linc00261 in pre‐eclampsia and its effect on trophoblast invasion and migration via regulating miR‐558/TIMP4 signaling pathway. Issue 8 (19th March 2019) - Cheng, Dan; Jiang, Shan; Chen, Jiao; Li, Jie; Ao, Liangfei; Zhang, Ying
Abstract: Pre‐eclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality but the exact underlying mechanisms of PE pathogenesis remain elusive. Accumulated data suggested that the long noncoding RNAs (lncRNAs) play important roles in the pathogenesis of PE. The present study identified the changes of lncRNA Linc00261 in PE and its effects on trophoblasts invasion and migration. Our results showed that the expression of Linc00261 was upregulated in placental tissues of PE women compared with those of healthy pregnant women. Overexpression of Linc00261 suppressed cell invasion and migration, induced cell apoptosis, and caused cell‐cycle arrest at G0 /G1 phase of HTR‐8/SVneo cells; while knockdown of Linc00261 had the opposite effects on the HTR‐8/SVneo cells. Mechanistic studies showed Linc00261 functioned as a competing endogenous RNA for miR‐558 in HTR‐8/SVneo cells, and miR‐558 was negatively regulated by Linc00261. The expression level of miR‐558 in the PE group was significantly lower than the control group, and the expression level of Linc00261 was negatively correlated with the expression level of miR‐558 in the placental tissues of women with PE. Furthermore, miR‐558 was found to negatively regulate the expression of TIMP metallopeptidase inhibitor 4 (TIMP4) via targeting the 3′ untranslated region in the HTR‐8/SVneo cells. Overexpression of miR‐558 increased HTR‐8/SVneo cell invasion and migration, which was attenuated by TIMP4 overexpression. More importantly, both overexpression of miR‐558 and knockdown of TIMP4 partially reversed the suppressive effects of Linc00261 overexpression on cell invasion and migration of HTR‐8/SVneo cells. Collectively, our results for the first time showed the upregulation of Linc00261 in the placental tissues of severe PE patients. The mechanistic results indicated that Linc00261 exerted the suppressive effects on the trophoblast invasion and migration via targeting miR‐558/TIMP4 axis, which may involve in the pathogenesis of PE. Abstract : Pre‐eclampsia (PE) is a leading cause of maternal and perinatal morbidity and mortality and the exact underlying mechanisms of PE pathogenesis remain elusive. Our study for the first time showed the upregulation of Linc00261 in the placental tissues of severe PE patients. The mechanistic results indicated that Linc00261 exerted the suppressive effects on the trophoblast invasion and migration via targeting miR‐558/TIMP4 (TIMP metallopeptidase inhibitor 4) axis, which may involve in the pathogenesis of PE.